Covid Conversations 2: Anne Bogart. (May 2021) - Bogart, Anne; Shevtsova, Maria
Abstract : Maintaining and nurturing an ensemble theatre have been Anne Bogart's foremost concerns in these past near-thirty years since she and Tadashi Suzuki founded the Saratoga International Theatre Institute (SITI) in 1992. Suzuki had established the Suzuki Company of Toga (SCOT) in 1976, making a secluded mountainous landscape of Japan its home to this day. Bogart's venture in the United States, although inspired by Suzuki's model of a production-based troupe of high artistic standards that, at the same time, developed its unique training methods, by no means merely duplicates its predecessor. In this Covid Conversation, Bogart briefly maps a segment of SITI's history, reflecting on the company's inter-arts endeavours with differing dance idioms and its engagement with Greek tragedy. She discusses the effects of the Covid pandemic on her troupe, also interrupting its performances of The Bacchae at the Guthrie Theatre in Minneapolis. Her most recent opera production, Tristan and Isolde, was closed for the same reason at the Croatian National Theatre – a key work in her portfolio of nineteenth-century grand opera as well as contemporary avant-garde opera. An acclaimed theatre director, Anne Bogart runs and teaches the Graduate Directing Programme at Columbia University in New York. At the SITI summer school in Saratoga, she and the company have workshopped the Viewpoints method that she has elaborated from Mary Overlie's six principles for theatre and dance training. Bogart's international workshops have further developed her method. She is the author of A Director Prepares (Routledge, 2001) and of many influential books that include (with Tina Landau) The Viewpoints Book (Theatre Communications Group, 2004). The Art of Resonance is forthcoming (2021, Bloomsbury). Maria Shevtsova is the Editor of New Theatre Quarterly whose most recent book is Rediscovering Stanislavsky (Cambridge University Press, 2020). The following conversation took place on 27 August 2020, was transcribed by Kunsang Kelden, and was edited by Maria Shevtsova. It is followed by a short coda announcing the transition of SITI into a resource centre.